Testing and temptation in Second Temple Jewish and early Christian texts - Stuckenbruck, Loren T.; Smith, Daniel L. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
In antiken jüdischen und frühchristlichen Schriften sind »Prüfung« und »Versuchung« unausweichlich ein Teil der menschlichen Erfahrung – von Eden über Massa bis zum Eschaton. Die hier versammelten Beiträge untersuchen die Rede und die Funktion des Prüfens und Geprüftwerdens in den Quellenschriften.InhaltsübersichtDaniel L. Smith/Loren T. Stuckenbruck: Introduction – Michael Francis: Philo of Alexandria on Testing and Temptation – Madison N. Pierce: Testing and Being Tested in the Epistle to the Hebrews – Loren T. Stuckenbruck: Eschatological Temptation the Enochic Way: A Note on 1 Enoch 94:5 – Todd R. Hanneken: Ten-Times-Tested Abraham in the Book of Jubilees – Susanne Luther: Preparing for Temptation in a Culture of Mutual Ethical Responsibility – Tzvi Novick: Life as Test: Reflections on m. 'Abot 2:4 and Related Texts – Andrew Bowden: »And the Mixed among Them Desired a Desire”: The Reception of Desire in Numbers 11 LXX in Greek Texts, Ending with the Apostle Paul – Jan Willem van Henten: The Triangle of Testing in the Wilderness – Daniel L. Smith: Testing the Child of God at the Beginning and until the End: ΠΕΙΡΑΣΜΟΣ and Theological Anthropology in Ancient Jewish and Christian Texts – Susan R. Garrett: (Not) Knowing Where I'm Going: Ignorance and Agony for Jesus and Job – Benjamin G. Wright III: Unbridled Libido: Ben Sira and the Billy Graham Rule